A Pale Baby With Blue Blood. Issue 10 (October 2015) - Berant, Ron; Ratnapalan, Savithiri
Abstract : Abstract: A previously healthy 9-month-old boy presented to the emergency department with sudden onset of pallor and reduced activity. A detailed history and initial blood tests revealed the diagnosis of oxidant stress–induced hemolysis caused by glucose-6-phosphate dehydrogenase deficiency. However, the child also had a second diagnosis that was revealed with additional testing. This case is described to illustrate the dual diagnosis and management guidelines for both potentially serious conditions.